2021
DOI: 10.3390/genes12030351
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Reactivity Symptoms Are a Core Feature of ADNP Syndrome Irrespective of Autism Diagnosis

Abstract: Background: Activity dependent neuroprotective protein (ADNP) syndrome is one of the most common single-gene causes of autism spectrum disorder (ASD) and intellectual disability, however, the phenotypes remain poorly described. Here we examine the sensory reactivity phenotype in children and adolescents with ADNP syndrome. Methods: Twenty-two individuals with ADNP syndrome received comprehensive clinical evaluations including standardized observations, caregiver interviews, and questionnaires to assess sensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
(53 reference statements)
2
13
0
Order By: Relevance
“…Additionally, regardless of DSM-5 ASD diagnosis, many individuals in our cohort presented with features of ASD. Most individuals, regardless of ASD status, presented with RRBs and sensory symptoms, a finding seen in other genetic NDDs ( 26 , 27 ). Both the SAND and the Sensory Experiences Questionnaire Version 3.0 (SEQ-3.0) indicated that individuals had high levels of sensory-seeking behaviors.…”
Section: Discussionmentioning
confidence: 74%
“…Additionally, regardless of DSM-5 ASD diagnosis, many individuals in our cohort presented with features of ASD. Most individuals, regardless of ASD status, presented with RRBs and sensory symptoms, a finding seen in other genetic NDDs ( 26 , 27 ). Both the SAND and the Sensory Experiences Questionnaire Version 3.0 (SEQ-3.0) indicated that individuals had high levels of sensory-seeking behaviors.…”
Section: Discussionmentioning
confidence: 74%
“…Using a comprehensive direct assessment of sensory symptomatology, this study established a distinct sensory reactivity phenotype in children with a PMS, characterized by global hyporeactivity across visual, tactile, and auditory modalities, and to a lesser degree, tactile and auditory sensory seeking. This sensory phenotype is distinct from iASD and other monogenic forms of ASD [ 21 , 30 ] and offers insight into the potential role of SHANK3 deficiency in sensory reactivity. Understanding sensory reactivity abnormalities in PMS in the context of known glutamatergic dysregulation may inform pharmacological treatment approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The SAND is a clinician-administered observation and corresponding caregiver interview that captures sensory symptoms based on DSM-5 criteria for ASD and is appropriate for individuals with varying levels of ability, including those with few to no words [ 20 ]. The SAND has been used successfully in other genetic forms of autism [ 21 ]; however, it has yet to be examined extensively in PMS. Establishing the utility of the SAND as a clinical outcome measure may have important implications for ongoing clinical trials in PMS.…”
Section: Introductionmentioning
confidence: 99%
“…Sensory processing, meaning how sensory signals, such as light, sound, touch, taste or smell are perceived, are commonly altered in many neurodevelopmental disorders [ 1 , 2 ]. For example, sensory processing differences have been described in non-syndromic Autism Spectrum Disorders (ASDs) [ 3 ], tic disorders [ 4 ], Fragile X syndrome [ 5 ], attention deficit hyperactivity disorder [ 6 ] and a limited number of syndromic ASDs [ 7 , 8 , 9 , 10 ]. Not surprisingly, the specific sensory phenotypes and distributions of sensory differences vary across diseases.…”
Section: Introductionmentioning
confidence: 99%